1975
DOI: 10.1002/mrc.1270070907
|View full text |Cite
|
Sign up to set email alerts
|

13C‐NMR‐Spektren von Monoterpenen

Abstract: Abstract-The 13C NMR spectra of nearly 100 rnonoterpenes show thatthey ar every useful for the characterisation of these compounds. This method is especially valuable for the elucidation of stereochemical problems. With the exception of a few cases the observed chemical shifts follow the common rules. The problems with measurements using shift reagents are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
63
0
2

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(84 citation statements)
references
References 4 publications
19
63
0
2
Order By: Relevance
“…Fractions that possessed fumigant toxicity, with similar TLC profiles, were pooled and further purified by preparative silica gel column chromatography (PTLC) until to obtain three pure compounds for determining structure ( Figure 1). The spectral data of β-myrcene (1) (1.2 g) matched with the previous report 14,15 . The data of β-ocimene (2) (1.7 g) matched with the previous report 14,16 .…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Fractions that possessed fumigant toxicity, with similar TLC profiles, were pooled and further purified by preparative silica gel column chromatography (PTLC) until to obtain three pure compounds for determining structure ( Figure 1). The spectral data of β-myrcene (1) (1.2 g) matched with the previous report 14,15 . The data of β-ocimene (2) (1.7 g) matched with the previous report 14,16 .…”
Section: Methodssupporting
confidence: 89%
“…The spectral data of β-myrcene (1) (1.2 g) matched with the previous report 14,15 . The data of β-ocimene (2) (1.7 g) matched with the previous report 14,16 . The spectral data were identical to the published data of α-phellandrene (3) (0.8 g) 14,16 .…”
Section: Methodssupporting
confidence: 89%
“…Compounds 2-8 were identified as geranial (2), 4) neral (3), 4) b-sitosterol (4), 5) oleanolic acid (5), 6) ursolic acid (6), 7) p-mentha-8-en-1,2-diol (7), 8) and colosolic acid (8) 9) by comparison of their spectral data with those reported. Compound 1 was identified by the analysis of its NMR spectra as limonen-10-al (1).…”
mentioning
confidence: 99%
“…The enols are diversely represented amongst physiologically active compounds (1)(2)(3)(4)(5)(6)(7)(8). Many important pheromones of the sex attractant (2-4) and the insect feedant types (1) possess enolic functions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the position and configuration of the double bonds are responsible for the structure-reactivity relationship (2). In addition, a large number of retinols and monoterpenes possess the hydroxy-isoprene unit (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%